TECHNICAL PROFESSIONAL INTERESTS OF PUPILS OF THE 9TH GRADE AT PRIMARY SCHOOLS - BILIKOVÁ, Veronika (Trends in education, 2013)
Author of the contribution deals with professional interests of pupils in the 9th grade of primary schools in Nitra. She was finding out the preferential order of professional interests of pupils. Via questionnaire "Semafor" she classified typology of personality of particular pupils. In connection to the weekly dotation for the subject Technology she wanted to find out whether there is any relation between higher weekly number of Technology lessons and increased interest of pupils in future profession.
Keywords: Professional interests; Technology; Primary school